A theoretical solution of the axial stiffness of a cylindrical shell with a circular plate. (September 2021) - Feng, Sheng; Yang, Baisong; Tian, Jiale; Yu, Lie
A structure of a cylindrical shell with a circular plate end cap is usually used in connect different shaft system and it is necessary to estimate the axial stiffness in order to analyze the vibration of the rotor system. This paper builds the model of this structure. The theoretical solution of the bending deflection of the circular plate and the cylindrical shell are deduced by using the classic theory of plates and shells, and the continuity boundary conditions at the junction of the circular plate and the cylindrical shell. Furthermore, the axial stiffness of the structure is solved through considering the relationship between the external force-bending deformation. Two different boundary conditions for the left side of the cylindrical shell is considered and their axial stiffness varying with the length of the cylindrical shell is calculated. For verification, a finite element model of the structure is built and analyzed. The theoretical results fairly coincide with the finite element ones.